OBTENÇÃO DE SENSORES DE TEMPERATURA DO TIPO NTC A PARTIR DE MISTURA MECÂNICA DE ÓXIDOS DE NÍQUEL E COBALTO - Silva, Edison Luiz Salgado (2011)
In this work it was characterized the microstructure and the electrical parameters of NTC temperature sensors, based on the mechanical mixing of niquel and cobalt oxides. Different proportions of this two materials (mol), was prepared and sintered at 1150C, 1200C, 1250C and 1300C. The microstructure was characterized by x-ray diffraction, MEV and EDS referring to the fases formed during the sintering, as well as, regarding grain size, the distribution of the chemical elements of this two oxides and the porosity of the final ceramic product. For the proportions of 10, 20, 30, 40, 50, 60, 80 e 90 (mol) of NiO on C3O4, and sintered on the four temperarures, it was obtained solid solution between niquel and cobalt oxides. Spinel phase, NiC2O4, was formed in the composition with 70 NiO (mol) at 1250C and 1300C, with segregation of CoO phase between the grain boundaries. The one phase composition with 60 (mol) NiO, sintered at 1250°C, and the composition with 70 (mol) NiO, sintered at 1300C, showed the best thermistor characteristics, by DC characterization. The values of beta factor, sensitivity and activation energy for the conductivity process (Ea), of the composition with 70 NiO was respectively 6203 K-1; -4,0 at (120C) and 0,53 eV.